First Report of Tomato mottle mosaic virus infecting Chinese snake gourd (Trichosanthes kirilowii) in China - Jin, Daoran (Plant disease, 2023)
Tomato mottled mosaic virus (ToMMV) was first identified in tomato in Mexico (Li et al. 2013). It belongs to the genus Tobamovirus and family Virgaviridae, and is a positive-sense single-stranded RNA virus. The viral genome contains about 6400 nucleotides, encoding four proteins, including the 126 K protein, 183 K protein, movement protein (MP) and coat protein (CP) (Tu et al. 2021). ToMMV mainly poses a serious risk to solanaceous crops. The virus-infected plants appear stunted growth and top necrosis, and the disease leaves show mottled, shrinkage and necrosis symptoms, resulting in a significant decline in tomato fruit yield and quality (Li et al. 2017; Tu et al. 2021). Chinese snake gourd (Trichosanthes kirilowii Maxim) is a perennial climbing herb in the family Cucurbitaceae, and the fruit, seed, peel and root can all be used as traditional Chinese medicine. In May of 2021, twenty-seven symptomless seedlings (developed from tissue culture plantlets) were randomly collected from nursery in Fengyang, Anhui Province. Total RNA of each sample was extracted, and RT-PCR was performed using degenerate tobamovirus primers Tob-Uni1 (5'-ATTTAAGTGGASGGAAAAVCACT-3') and Tob-Uni2 (5'-GTYGTT GATGAGTTCRTGGA-3') (Letschert et al. 2002). Amplicons with expected size were obtained from 6 of 27 samples and sequenced. Alignment results showed that the nucleotide sequence identities ranged from 98.7 to 100% with all ToMMV isolates deposited in NCBI GenBank. Then, ToMMV coat protein (CP) gene was amplified using specific primers CP-F (5'-ATGTCTTACGCTATTACTT CTCCG-3') and CP-R (5'-TTAGGACGCTGGCGCAGAAG-3'). The CP fragment was obtained and sequenced. Sequence alignment indicated that CP sequence of isolate FY (GenBank accession no. ON924176) exhibited a 100% identity with ToMMV isolate LN (MN853592.1). The anti-ToMMV polyclonal antibody (PAb) was prepared by the author (S.L.) by immunizing rabbit with purified virus from Nicotiana benthamiana, and serological tests (dot-enzyme linked immunosorbent assay, Dot-ELISA) of RNA-positive T. kirilowii leaf samples using anti-ToMMV PAb were also positive. To fulfill a Koch's postulate, a pure culture of ToMMV was obtained from N. benthamiana using infectious cDNA clone of ToMMV (Tu et al. 2021), and then healthy T. kirilowii plants were mechanically inoculated with a prepared inoculum from ToMMV-infected N. benthamiana, as described previously (Sui et al. 2017). T. kirilowii seedlings showed chlorosis and leaf tip necrosis symptoms at 10 and 20 day post-inoculation respectively, and ToMMV infection on symptomatic plants was also verified by RT-PCR detection using primers CP-F and CP-R. These results demonstrated that T. kirilowii is a host of ToMMV under natural conditions, which might threaten the production of this medicinal plant. The seedlings from nursery appeared to be asymptomatic, but the plants showed chlorosis and necrosis symptoms after indoor inoculation. In qRT-PCR analysis, viral accumulation level in greenhouse-inoculated plants was a 25.6-fold of that in field-collected samples, which may be the reason of different symptom expression between field samples and inoculated samples. ToMMV has now been detected from the solanaceous (tomato, pepper and eggplant) and leguminous (pea) crops in the field (Li et al. 2014; Ambrós et al. 2017; Zhang et al. 2022). To our knowledge, this is the first report of natural infection of ToMMV in T. kirilowii as well as its natural infection on Cucurbitaceae plants